Pengaruh Penerapan Metode Problem Based Learning Terhadap Sikap Ilmiah dan Hasil Belajar Biologi Siswa Kelas VII MTs NW 01 Kembang Kerang - Sri Ismiani; Syukri Syukri; Dwi Wahyudiati (Universitas Islam Negeri Mataram, 2017)
This study aims to determine the effect of the application of Problem Based Learning method on the scientific attitude and learning results of 7th grade students in MTs NW 01 Kembang Kerang towards the study materials in biology. This research is a Quasi Experiment (Pseudo-experiment) that was designed to use both Pre-test and Post-test control groups. The study samples were taken randomly from two different classes i.e. VII C as the experimental group and VII D as the control. The output of this study was presented in a scientific attitude of the students, analysed by descriptive test as well as the learning results of the students which were observed by unpaired T-test. The results showed that there was a significant difference in the scientific attitude of the students in the experimental class compared to the control one where the conventional method was applied. This was shown by the difference in the variance of students’ attitude (86.6% in the experimental group; 47.2% in the control). There was also a significant difference in the learning results of these students. The T-test was performed and it has been shown that the significance value was 0.019 < 0.05. To summarize this study, Problem Based Learning method had a significance impact in the scientific attitude and learning results of the students, this suggested that this method can be used as an alternative technique to teach biology in school.